Navigation - Symphony in the Flint Hills, Inc. (Symphony in the Flint Hills, 2019)
Introduction: "Too few people care about the stars...Old people know the stars and children love them...Stars are no longer regarded as useful, therefore they have been abandoned. A century ago people knew them better...Culture was given precedence over practicality...I find the old people can call the stars by name, while the young do not know them." -- Annie Jump Cannon, 1924. According to ancient tradition the Osages (in their own language, the Wahzhazhe) came to earth from the stars. Perhaps they were the first to comprehend that we are all made of stardust.